Characterization of Cre recombinase mouse lines enabling cell type‐specific targeting of postnatal intervertebral discs. Issue 9 (23rd January 2019) - Zheng, Yixin; Fu, Xuejie; Liu, Qingbai; Guan, Shengqi; Liu, Cunchang; Xiu, Chunmei; Gong, Tingting; Jin, Hongting; Saijilafu,; Zhang, Zunyi; Chen, Di; Chen, Jianquan
Abstract: Cre/loxP technology is an important tool for studying cell type‐specific gene functions. Cre recombinase mouse lines, including Agc1‐CreER T2, Col2a1‐Cre ; Col2a1‐CreER T2, Shh‐Cre, Shh‐CreER T2, and Osx‐Cre, have been proven to be valuable tools to elucidate the biology of long bones, yet the information for their activity in postnatal intervertebral disc (IVD) tissues was very limited. In this study, we used R26‐mTmG fluorescent reporter to systematically analyze cell specificity and targeting efficiency of these six mouse lines in IVD tissues at postnatal growing and adult stages. We found that Agc1‐CreER T2 is effective to direct recombination in all components of IVDs, including annulus fibrosus (AF), nucleus pulposus (NP), and cartilaginous endplate (CEP), upon tamoxifen induction at either 2 weeks or 2 months of ages. Moreover, Col2a1‐Cre targets most of the cells in IVDs, except for some cells in the outer AF (OAF) and NP. In contrast, the activity of Col2a1‐CreER T2 is mainly limited to the IAF of IVD tissues at either stage of tamoxifen injection. Similarly, Shh‐Cre directs recombination specifically in all NP cells, whereas Shh‐CreER T2 is active only in a few NP cells when tamoxifen is administered at either stage. Finally, Osx‐Cre targets cells in the CEP, but not in the NP or AF of IVDs tissues at these two stages. Thus, our data demonstrated that all these Cre lines can direct recombination in IVD tissues at postnatal stages with different cell type specificity and/or targeting efficiency, and can, therefore, serve as valuable tools to dissect cell type‐specific gene functions in IVD development and homeostasis. Abstract : Six Cre recombinase mouse lines were characterized and shown to direct recombination in IVD tissues at postnatal stages with different cell type specificity and/or targeting efficiency. These mouse lines can serve as valuable tools to dissect cell type‐specific gene functions in IVD development and homeostasis.